Humanis dalam Mendidik (Analisis Terapan Aliran Psikologi Humanistik) - Ellyana Ilsan Eka Putri (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2018)
Humanistic approach arouse in the 1940s as thedissatisfaction reactions to psychoanalysis and behaviouristicapproaches. As one of the approach in psychology, it isrelatively alive and continuously generates relevant concepts topsychology research fields, that emphasizes to selfactualization awareness and positive things about humanism.This article will be portraying high-profile figures on humanisticand their relevant theories to educational psychology and willbe concluded with the application of humanistic psychology ineducational fields, especially in the learning process